Efectos que genera la contaminación acústica en los turistas que visitan el centro histórico de Trujillo. - Lauriano Pizarro, Elvira (2016)
In the present investigation the effects that the Acoustic Pollution generates in the tourists who visit the Historic Center of Trujillo have been identified, these are of two types, the psychological and the physiological. In the psychological it was possible to determine the existence of three levels, emotional, cognitive and behavioral; And the physiological the auditory and non-auditory._x000D_ These psychological effects generated by the noise, present in the tourists in great percentage, in the emotional with a dissatisfaction 40%, causing them displeasure; In the cognitive the difficulty of making decisions 37%, making them difficult to decide to continue with the tourist activities in the Historical Center of Trujillo; And in the behavioral loss of interest in performing some activities 50%, that is to say, loses the desire to visit. The physiological effects occur in a large percentage of the auditory that leads to a degree of hearing loss 51% when the tourist is exposed to high noise levels generated in an instant and in the non-auditory headache 38%, Which enters the ear like a buzz._x000D_ The applied methodology was based on the Deductive - Inductive method and the Ethnographic method, also by means of indicators, the percentages generated by the noise were obtained, finding the Historical Center with high noise index that exceeds what was established, Of Measurement Evaluation in specific points in the Historical Center, taking into account the Tourist Attractions most visited by the tourists, as well as the specialists in the area of medicine in Otorhinolaryngology and Psychology were interviewed in order to know if the tourist can Have any effect on your health whether physical or mental.